Peran Well-Being dalam Hubungan antara Job Demand-Resources Dengan Kinerja - Leliantika Handitya Deastri; Revi Diana; ruchan yulabi; Athiah Listyowati (Universitas Muhammadiyah Sidoarjo, 2026)
This study aims to examine the relationship between job demands and job resources with employee well-being and performance. The research was conducted on employees of the Ministry of Finance, with data collected through a survey method using convenience sampling techniques. A total of 3,403 respondents participated in the survey. Based on analysis using Smart PLS, the findings indicate a negative correlation between job demands and well-being, and a positive correlation between job resources and well-being. Additionally, well-being is positively correlated with performance. Thus, well-being serves as a mediating variable in the relationship between job demands and job resources with performance. Highlights• Job demands show an inverse association with psychological condition levels• Job resources demonstrate a direct positive association with psychological condition levels• Psychological condition acts as a mediating mechanism linking work characteristics and performance KeywordsJob Demands; Job Resources; Well Being; Employee Performance; Mediation